Is the answer blowin' in the wind (auctions)? An assessment of the Italian support scheme. (November 2017) - Cassetta, Ernesto; Monarca, Umberto; Nava, Consuelo Rubina; Meleo, Linda
Abstract: This article proposes a quantitative data-based assessment of the onshore wind auctions conducted in Italy from 2012 to 2016. Our objective is to provide new insights in the ongoing debate on policy measures to promote renewable energy sources. Italian wind auction design is examined by firstly investigating its overall outcomes in terms of cost efficiency and policy effectiveness. Determinants affecting awarded tariffs are then empirically analysed further to explore the role of project-related and firm-specific factors as well as different auction design elements. The extreme simplicity of the auction design undoubtedly has promoted competition, encouraging many project developers to bid and reducing support both in static and dynamic terms. Results provide evidence that localisation factors did not constitute a competitive constraint. From a policy perspective, the administratively setting of ceiling prices is a major issue when wind resources are widely available and auctioned capacity is not sufficiently high. While not limiting competition, the effects of pre-qualification criteria on the realisation rate deserve further analysis. However, doubts emerge on the policy effectiveness of the current support scheme which makes difficult to control the total amount of support provided thus likely causing stop-and-go cycles of financing and potentially favouring distorted bidding behaviour. Highlights: A quantitative data-based assessment of Italian on-shore wind auctions is provided. Our investigation outlines effectiveness and cost-efficiency of current auction design. Project-related, firm-specific and auction design determinants of awarded base tariffs are also explored. Results provide relevant findings for better understanding of auction potential outcomes in RES context.